2006
DOI: 10.1021/ac060138l
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Measurement of Oligomeric Species in Secondary Organic Aerosol with the Aerosol Time-of-Flight Mass Spectrometer

Abstract: Real-time detection of oligomers in secondary organic aerosols has been carried out with an aerosol time-of-flight mass spectrometer sampling particles generated in a smog chamber. The photooxidation products of 1,3,5-trimethylbenzene and NOx were studied over a range of initial 1,3,5-trimethylbenzene concentrations (137-1180 ppb), while keeping the 1,3,5-trimethylbenzene to NOx ratio nearly constant. The photooxidation products of a mixture of alpha-pinene (initial concentration 191 ppb), 1,3,5-trimethylbenze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 23 publications
(70 reference statements)
7
93
0
1
Order By: Relevance
“…These ions are absent for the Oligomer class identified in this work, suggesting that these particles may be relatively fresh compared to those observed by Denkenberger et al (2007). The rate of formation of detectable oligomers in secondary organic aerosol simulation chamber studies is typically of the order of hours (Kalberer et al, 2004;Gross et al, 2006), although studies performed in the absence of seed aerosol are often characterised by long induction periods while oxidation products reach high enough concentrations to induce nucleation Gross et al, 2006;Healy et al, 2008). In the case of Denkenberger et al (2007), increased particle acidity was observed to accelerate oligomer formation.…”
Section: Ecoc and Oligomermentioning
confidence: 76%
See 1 more Smart Citation
“…These ions are absent for the Oligomer class identified in this work, suggesting that these particles may be relatively fresh compared to those observed by Denkenberger et al (2007). The rate of formation of detectable oligomers in secondary organic aerosol simulation chamber studies is typically of the order of hours (Kalberer et al, 2004;Gross et al, 2006), although studies performed in the absence of seed aerosol are often characterised by long induction periods while oxidation products reach high enough concentrations to induce nucleation Gross et al, 2006;Healy et al, 2008). In the case of Denkenberger et al (2007), increased particle acidity was observed to accelerate oligomer formation.…”
Section: Ecoc and Oligomermentioning
confidence: 76%
“…13). ATOFMS particle mass spectra containing similar high mass negative ion signals have been identified as oligomer-containing, both in simulation chamber experiments and in ambient datasets (Gross et al, 2006;Denkenberger et al, 2007). In the latter study, several different aged particle types were found to contain oligomers, including vanadium-rich, amine-rich, organic carbon, and internally mixed organic/elemental carbon particles.…”
Section: Ecoc and Oligomermentioning
confidence: 77%
“…In general, HULIS are considered refractory organic molecules that can only be thermally vaporised from 400-600 • C ( Andreae and Gelencser, 2006). Recent smog chamber experiments have shown that the ATOFMS can detect oligomeric species (Gross et al, 2006) whilst the AMS provides other very useful information but may not be able to detect oligomeric species well . Additionally, as the AMS is responding to aerosol mass, it will inevitably be of less sensitivity towards minor components of the aerosol.…”
Section: Aerosol Characterizationmentioning
confidence: 99%
“…Carbonyl containing species are known to participate in aldol, acetal, and esterification reactions, which form low volatility compounds that add to SOA mass. Field and laboratory studies have also yielded evidence for the formation of high molecular weight products within SOA (Gross et al, 2006;Reinhardt et al, 2007;Denkenberger et al, 2007) and it is well known that GL will polymerize in the presence of water (Whipple, 1970;Loeffler et al, 2006). These properties of GL, together with its production via oxidation of many VOCs, have inspired chamber investigations into GL partitioning onto a variety of seed particles (Jang et al, 2002;Liggio et al, 2005a,b;Kroll et al, 2005;Corrigan et al, 2008;Volkamer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%